2021
DOI: 10.1177/15459683211054175
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Based Stroke Rehabilitation: Clinical Considerations Following the COVID-19 Pandemic

Abstract: Background. The COVID-19 pandemic attributable to the severe acute respiratory syndrome virus (SARS-CoV-2) has had a significant and continuing impact across all areas of healthcare including stroke. Individuals post-stroke are at high risk for infection, disease severity, and mortality after COVID-19 infection. Exercise stroke rehabilitation programs remain critical for individuals recovering from stroke to mitigate risk factors and morbidity associated with the potential long-term consequences of COVID-19. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
(251 reference statements)
0
1
0
Order By: Relevance
“…In their study, Qureshi et al analyzed over 27,000 hospitalized patients and found that those who were diagnosed with COVID-19 and experienced an acute ischemic stroke exhibited a twofold elevation in the likelihood of being discharged to a non-home destination or death ( 106 ). The poor prognosis of COVID-19 stroke patients might be associated with more severe onset symptoms and lack of effective rehabilitation during the epidemic ( 101 ). Another explanation for the worsening stroke prognosis in COVID-19 patients is probably the diminished use of acute stroke therapies such as tissue fibrinogen activator (t-PA) and mechanical thrombectomy (MT).…”
Section: Covid-19-associated Cerebrovascular Complicationsmentioning
confidence: 99%
“…In their study, Qureshi et al analyzed over 27,000 hospitalized patients and found that those who were diagnosed with COVID-19 and experienced an acute ischemic stroke exhibited a twofold elevation in the likelihood of being discharged to a non-home destination or death ( 106 ). The poor prognosis of COVID-19 stroke patients might be associated with more severe onset symptoms and lack of effective rehabilitation during the epidemic ( 101 ). Another explanation for the worsening stroke prognosis in COVID-19 patients is probably the diminished use of acute stroke therapies such as tissue fibrinogen activator (t-PA) and mechanical thrombectomy (MT).…”
Section: Covid-19-associated Cerebrovascular Complicationsmentioning
confidence: 99%